The Effect of Health Hardiness on Fear of COVID-19 in Nurses: Investigating the Mediating Role Tolerance of Emotional Distress - Nahid Ramak; Adineh Bazgouneh; Elahe Ghasempour; Zeinab Sadeghkhani; Eshaqh Sam Khania; Farshid Bibak; Alireza Sangani (Gonabad University of Medical Sciences, 2022)
Background: Nurses have the most level of communication with patients with COVID-19 who are always afraid of the disease and its consequences. Therefore, the present study aimed at investigating the effect of health hardiness on fear of COVID-19 in nurses with the mediating role tolerance of emotional distress. Methods: The method of this research was descriptive-correlational. The statistical population of the present study consisted of all 351 female nurses of Imam Khomeini and Taleghani hospitals in Urmia in spring 2021. According to the target population, 205 nurses were selected based on Krejcie and Morgan's table and according to the available method. In this study, the Fear of COVID-19 Questionnaire developed by Ahorsu et al. [2020], the Health Hardiness Questionnaire designed by Gebhardt et al. [2001], and the Emotional Distress Tolerance Questionnaire developed by Simons and Gaher [2005] were used. Data were analyzed by Pearson correlation coefficient and stepwise regression. Results: The findings showed that health hardiness and tolerance of emotional distress were involved in fear of COVID-19. Also, according to the values ​​obtained, health hardiness had an effect of -0.364 on fear of COVID-19, and tolerance of emotional distress had an effect -of -0.178 on fear of COVID-19 [p≤0.01]. Health hardiness an effect equal to -0.528 on fear of COVID-19 with the mediating role of tolerance of emotional distress. Conclusion: This study showed that cognitive factors in proportion to emotional factors have a greater effect on the fear of COVID-19 in nurses.